Prediction Model for the Toxicity of pyridinium Based Ionic Liquids Towards vibrio fischeri Bacteria Using QSAR Models - Md Saad, Luqman (IRC, 2016)
Ionic liquid is a salt in a liquid form that comprises of two equal ions which are anion and cation. Nowadays, the applications of ionic liquid in industry have growth rapidly, it is because the ability to replace conventional volatile organic solvent. This innumerable utilization of ionic liquid is due to its properties that produce negligible vapor pressure and also non-inflammability. These remarkable properties also reduce and eliminate the potential of air pollution. The understanding of ionic liquids which is green in not true, it was early reported that some of synthesized ILs are highly hazardous.